ANALISIS BEBAN KERJA TERHADAP KARYAWAN PENYEMPROTAN TANAMAN SAWIT DI PT. EQUALINDO MAKMUR ALAM SEJAHTERA KECAMATAN TELEN KABUPATEN KUTAI TIMUR PROVINSI KALIMANTAN TIMUR - Muhammad Prayogo Bima Pratama; Elisa Herawati; Fathiah Fathiah (JURNAL AGRIMENT, 2021)
The purpose of this study was to analyze the duties of spraying employees at work starting from the daily routine during work and then to analyze the respondents based on their respective characteristics starting from education, age, height, weight and work experience.The method used in observing the activity and working time of spraying employees is a census by observing all of the spraying employees as many as 18 people.The results of the calculations carried out are calculating the distribution of productive, unproductive and personal time of spraying employees for 8 hours of work so that the average productive working time of 18 samples within 8 hours of work is 85.1% and 11.5%. for unproductive time and 3.4% for employee personal time. In addition, the result of the average time for completing tasks in 1 year is 136,320 minutes divided by the working time in a year that has been determined by the company, which is 114,380 minutes and multiplied by the number of respondents as many as 18 people which results in 15.10 or the same as 15 people .The results of this study are expected to be useful for those who read or for those who want to develop existing methods into better and more effective methods and can be used as an evaluation in planning and determining the needs of spraying employees as a consideration and evaluation in the future.